Understanding the linkages between migration and household food security in India. (24th February 2017) - Choithani, Chetan
Abstract: This paper argues for the need to integrate migration in future food policy research and practice and, in doing so, examines the role of internal migration as a livelihood strategy in influencing food security among rural households. Migration has become a key component of livelihood strategies for an increasing number of rural households across the developing world. Importantly, there is emerging consensus among academics and policy makers on migration's potentially positive effects in reducing poverty and promoting sustainable human development. Concurrently, the significance of the catch‐cry 'food security for all' as an important development objective has been growing, particularly since the 2007–08 global food crisis. However, academic and policy discussions on these two issues have tended to proceed largely in silos, with little attention devoted to the relationship they bear with each other. Using primary survey data collected from 392 rural households from a district in western Bihar in India, this paper seeks to fill this gap in relational dynamics. It first reviews plausible reasons for this disconnect between migration and food security in the wider developing countries' context, and then draws on a primary survey of rural Indian households to provide empirical household‐level insights on the linkages between people's movements and households' capacity to secure food. In particular, the paper focuses on the often‐overlooked role of migrants' remittances for food security of rural households at points of origin. The findings show that, by equipping households with improved purchasing power and enabling investment in agriculture, remittances contribute positively to household food security.